Specialization, Diversity, and Indian Manufacturing Growth - Ghani, Ejaz; Kerr, William R.; Tewari, Ishani (World Bank, Washington, DC, 2014)
This paper examines the specialization and diversity of manufacturing industries within Indian districts. Prior to India's recent economic growth and liberalization, specialization levels in 1989 were substantially higher than similar metrics calculated for the United States. From 1989 to 2010, average specialization levels for Indian districts declined to a level that is now quite comparable to the United States. Diversity levels similarly increased. Specialization and diversity levels in India are becoming more persistent with time. Manufacturing plants display higher productivity in districts that display both properties. From 1989 to 2010, manufacturing employment growth was higher in districts that were more specialized at the start of the period.